#TITLE_ALTERNATIVE# - (NIM : 131 13 100), ALBERT
Coupled machineries are widely used in industry. They always experience shaft misalignment. Based on practical experiences, shaft misalignment causes vibration at frequency 2, 3, 4, and 6XRPM. But, the phenomenon why vibration occurs with such characteristics has not been explained completely. These vibration characteristics can be understood better if the fluctuation of the excitation force due to misalignment is known. This fluctuation of force can be estimated from shaft's deflection or orbit. Based on the background, this final year project has objective to design and produce an apparatus capable of visualizing shaft's orbit when shaft operates at very low rotational speed. This final year project focuses on investigating shaft's orbit caused by parallel misalignment. To investigate shaft's orbit, there are two types of coupling that are used in these tests, those are jaw coupling and Oldham coupling. In this project, shaft that is more flexible than the bearing is used so that shaft's orbit could be observed visually. Shaft's orbit can be plotted by measuring shaft’s deflection on the horizontal and vertical axis at rotational speed about 1,5 – 2 rpm so that dynamic forces of the shaft can be neglected. The shaft’s deflection is measured using LVDT (Linear Variable Differential Transformer) sensors while data processing is conducted using Matlab software. From the experiment results, it is concluded that shaft's orbit which occurs on apparatus could not be observed visually. Experiment result using jaw coupling shows that shaft’s orbit does not get bigger when the offset is increased. Meanwhile, experiment result using Oldham coupling shows that orbit's size changes and produces small loop when the offset is increased. For better results, the coupling that is far more flexible than the shaft should be used in the future research.